Scalable analysis of Big pathology image data cohorts using efficient methods and high-performance computing strategies. Issue 1 (December 2015) - Kurc, Tahsin; Qi, Xin; Wang, Daihou; Wang, Fusheng; Teodoro, George; Cooper, Lee; Nalisnik, Michael; Yang, Lin; Saltz, Joel; Foran, David
Abstract Background We describe a suite of tools and methods that form a core set of capabilities for researchers and clinical investigators to evaluate multiple analytical pipelines and quantify sensitivity and variability of the results while conducting large-scale studies in investigative pathology and oncology. The overarching objective of the current investigation is to address the challenges of large data sizes and high computational demands. Results The proposed tools and methods take advantage of state-of-the-art parallel machines and efficient content-based image searching strategies. The content based image retrieval (CBIR) algorithms can quickly detect and retrieve image patches similar to a query patch using a hierarchical analysis approach. The analysis component based on high performance computing can carry out consensus clustering on 500, 000 data points using a large shared memory system. Conclusions Our work demonstrates efficient CBIR algorithms and high performance computing can be leveraged for efficient analysis of large microscopy images to meet the challenges of clinically salient applications in pathology. These technologies enable researchers and clinical investigators to make more effective use of the rich informational content contained within digitized microscopy specimens.